THEMATIC PROGRESSIONS OF THE 2015 TEFLIN ARTICLE ABSTRACTS IN APPLIED LINGUISTICS - Reski Oktaviani Yuned; Azwandi .; Arono . (JOALL (Journal of Applied Linguistics and Literature), 2016)
Coherence is one of the characteristic of good academic writing, including abstract that represent the whole content of research article in order to be able to show what messages want to be expressed in the abstract. This study investigated the English abstract TEFLIN in applied linguistisc written by Indonesian speaker in its coherence by analyzing the theme and rheme. This study focuses on (1) identifying the theme which are dominantly used in 2015 TEFLIN  article  abstracts  written  by  non-native  speaker  of English (2) identifying thematic progressions which are dominantly used in 2015 TEFLIN article abstracts written by non-native speaker of English (3) finding  out  coherences’ quality of the research  article  abstract  section  in 2105 TEFLIN article abstracts in applied linguistic  based on thematic  progression.  This study  was designed by  using descriptive qualitative. The results show that the type of theme dominantly used in 2015TEFLIN article abstracts written by non-native speaker of English is topical theme, not all  non-native  speakers  of  English  use  textual  theme,  and  just  a  few  of  them  useinterpersonal theme. In addition, Zig Zag pattern in thematic progression is dominantlyused then followed by reitaration theme, and the last Multiple (Split) pattern, none of the abstracts use Derived TP pattern. Most of the  research  article  abstract  section   in TEFLIN abstracts in applied linguistic have fair quality, just a few included to less quality, none of them was catagorized as good and poor quality. It can be concluded that English abstracts of TEFLIN in applied linguistisc written by Indonesian speakers can be catagorized as good abstract based on their coherence.